Identities and Linguistic Preferences in Selva Central Communities - Falcón Ccenta, Pedro Manuel (2018)
The purpose of the study is to analyze from the mentalist theoretical perspective, the languages preferences of the indigenous bilingual Amazonian settlers in affective, cognitive and sociocultural terms. For this, the factors age, sex, schooling and origin are evaluated that condition the positive or negative attitudes towards the native languages and towards Spanish. In addition, these factors compromise the identities, levels of self-esteem, socio-cultural supports. It also allows, through the evaluation of the variables of influence in the languages preferences of the Amazonian bilingual populations, to understand more objectively the value of indigenous users in relation to their own language and to Spanish in connection with elements of socio-cultural identification or distancing themselves from their group that with no doupt, compromises the vulnerability of the involved languages.